2022
DOI: 10.3389/fgene.2022.814264
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Genomic Predictions in Small Breeds by Construction of Genomic Relationship Matrix Through Variable Selection

Abstract: Genomic selection has been increasingly implemented in the animal breeding industry, and it is becoming a routine method in many livestock breeding contexts. However, its use is still limited in several small-population local breeds, which are, nonetheless, an important source of genetic variability of great economic value. A major roadblock for their genomic selection is accuracy when population size is limited: to improve breeding value accuracy, variable selection models that assume heterogenous variance ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Feature selection and ML learners have the power to deal with heterogeneous and large datasets, providing prediction accuracies and detecting genomic regions that impact the relationships between genotype and phenotype [ 30 , 31 ]. Efficient feature selection from GBM enables the preselection of SNPs with biological relevance to the target trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feature selection and ML learners have the power to deal with heterogeneous and large datasets, providing prediction accuracies and detecting genomic regions that impact the relationships between genotype and phenotype [ 30 , 31 ]. Efficient feature selection from GBM enables the preselection of SNPs with biological relevance to the target trait.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted that ML, such as random forest (RF), support vector regression (SVR), gradient boosting machine (GBM), artificial neural networks (ANN), and stacking ensemble learning, can be used for GP, and outperform parametric models (i.e., GBLUP and Bayesian regression) in situations where the reference population is small [ 26 29 ]. On the one hand, ML techniques have also been explored as a potential strategy for variable selection and then used in genomic BLUP (GBLUP) [ 30 , 31 ]. On the other hand, Azodi et al [ 32 ], with data on plants, and Bellot et al [ 33 ], with human data, found that some ML models (e.g., deep neural networks) had a lower stability (i.e., show variation in prediction accuracy when trained on different validation designs or populations) than linear models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies adopted different strategies to preselect predictors by directly excluding uninformative markers via machine learning [ 45 47 ] or assigning weights to markers according to their contributions to trait variability [ 48 ]. Piles et al [ 47 ] and Li et al [ 49 ] showed that feature selection strategies improved the predictive ability of complex traits.…”
Section: Discussionmentioning
confidence: 99%
“…S 5 –S 9 ). Fragomeni et al [ 50 ] and Mancin et al [ 45 ] highlighted the advantages of removing non-informative SNP, where better accuracy was achieved by constructing the G matrix by considering the window region where the QTL was identified or by using only QTL information.…”
Section: Discussionmentioning
confidence: 99%